Utilizing family life education as a resource for grandparents raising grandchildren: a qualitative study - Gardiner, Jessie (Kansas State University, 2014)
The number of grandparents who are taking over the responsibility of raising their grandchildren is increasing over time. Despite society’s reliance on them, society is failing to meet the needs of these families. Grandparents consistently lack the necessary resources that could reduce and minimize their stress in what is usually an unexpected family situation. Family Life Education has failed to meet the needs of grandfamilies. Using Family Stress Theory as a theoretical framework, this study asked the question How can Family Life Education be used as a resource for grandparents raising grandchildren to avoid crisis? Focus groups and individual interviews were used to gather qualitative data from grandparents who are currently raising their grandchildren near a midwestern university. Findings suggest grandparents raising grandchildren could benefit from education regarding finding resources and answers to questions as they navigate the many systems they are involved with, communicating and guiding their grandchildren, balancing and maintaining the shifting family dynamics and changing family relationships, information regarding the growth and development of children across the lifespan, and education regarding content that is unique to their family situation. However there are multiple barriers that participants identified toward the utilization of FLE. Ultimately, there is a lack of collaboration among services for grandparents raising grandchildren and they lack support that could potentially come from support groups. Impact and implications for practice, research and policy were discussed. Strengths and limitations of the study were also presented.
Keywords: Family life education; Grandparents raising grandchildren; Grandfamilies; Family stress theory; Adult Education (0516); Gerontology (0351); Social Research (0344)